Polymer nanocomposites : - Koo, Joseph H. (McGraw-Hill, 2006)
Understand the principles, applications, and limitations of a cutting-edge materialBased on the author's 26 years of experience in the field of Nanotechnology, this reference offers researchers and materials scientists a complete reference to the physical concepts, techniques, applications and principles underlying one of the most researched materials. Keeps you abreast of the latest trends, developments, and commercial applications